2022
DOI: 10.55251/jmbfs.1837
|View full text |Cite
|
Sign up to set email alerts
|

ETHANOL EXTRACT OF Basella alba Linn MODULATES ACRYLAMIDE-INDUCED OXIDATIVE STRESS IN WISTAR RATS

Abstract: Acrylamide (AA), a common toxicant in processed foods is associated with cancer development via induction of oxidative stress. Therefore, the need for a potent antioxidant substance or compound that could ameliorate this toxic effect. Basella alba has been reported to have medicinal properties, and in this study, the anti-oxidative potentials of ethanol leaf extract of Basella alba (ELEBa) were assessed against oxidative stress induced by acrylamide in male Wistar rats (120-150g). Twenty (20) animals were grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The methanol extract showed significant free radical scavenging activity in various assays, with DPPH being the most effectively neutralized (up to 94.8%) [45]. Adewale et al [46] investigated Basella alba extract could protect rats from acrylamide, a toxin found in processed foods. They found that the ethanol extract significantly reduced markers of kidney and liver damage in rats exposed to acrylamide.…”
Section: Anti-oxidant Propertiesmentioning
confidence: 99%
“…The methanol extract showed significant free radical scavenging activity in various assays, with DPPH being the most effectively neutralized (up to 94.8%) [45]. Adewale et al [46] investigated Basella alba extract could protect rats from acrylamide, a toxin found in processed foods. They found that the ethanol extract significantly reduced markers of kidney and liver damage in rats exposed to acrylamide.…”
Section: Anti-oxidant Propertiesmentioning
confidence: 99%
“…At 100µg/ml concentration, the percentage cell viability in Jurkat and A549 cells was found to be 41.78±1. 25 Serum was analyzed for hepatic and renal function biomarkers in the treated animals. The treatment with 100 and 250mg/kg body weight significantly reduced the elevated renal and hepatic biomarkers.…”
Section: Phytochemicals Reported In the Plantmentioning
confidence: 99%